A Systematic Review Of Primary Ankle Arthrodesis In The Treatment Of Pilon Fractures. (June 2021) - Nicholas, P.R.M.; Carter, R.; Chan, P.; Jamal, B.
Highlights: Primary ankle arthrodesis is a method of which can be used to treat pilon fractures. It involves restoring the articular surface and reconstituting mechanical alignment to produce a satisfactory outcome. There is a current lack of literature surrounding the topic and this paper serves as a benchmark for future studies. Primary ankle arthrodesis yields reasonable results compared to open reduction internal fixation and external fixation. Abstract: Background: Pilon fractures are severe, intra-articular and comminuted fractures to the distal tibia. They are uncommon injuries and are often associated with fibular fractures. The optimal management of these fractures is widely debated. Open reduction and internal fixation (ORIF) and external fixation have been used to treat these fractures. Ankle arthrodesis is often used in the latter stages of management for end-stage ankle arthritis. The aim of this systematic review was to identify the outcomes associated with using primary ankle arthrodesis in pilon fractures. Methods: Ovid Medline and PubMed were searched from the inception of their databases until October 2018. Eligible literature for use in our review included patient cohorts that had been operated in the form of primary ankle arthrodesis. All relevant data was included that met the inclusion criteria. The demographic of the patients with pilon fractures and this operative management were identified. The outcomes of interest were fusion rate, infection rate, length of follow-up and patient reported outcomes. 8 papers were deemed eligible for review. Results: Of the 8 papers that were eligible, 6 were retrospective studies, 1 was a case report and 1 was an abstract. There were a total of 109 patients included. Fusion rate was 100% in 5 of the studies. 6 of the 7 studies that reported on infection rate had no post-operative infections. Outcome assessment scores were used in 5 of the studies. The SF-36 score, the FOAS and the AOFAS were used. Conclusions: This review shows that primary ankle arthrodesis yields reasonable results in the management of pilon fractures. However, the quantity and quality of current literature is not sufficient and further studies with larger cohorts and longer follow-up times are warranted.